Anxiety Level Differences Between The Face Of Labour And Multigravida Primigravida - Eka Roisa Shodiqoh; Fahriani Syahrul (Universitas Airlangga, 2014)
Condition before childbirth is one thing that can cause anxiety. The process of giving birth is not always only somatic, but also psychosomatic. It is because many psychological elements affect the process of giving birth. This study aimed to analyze the differences in the level of anxiety in facing childbirth between primigravida and multigravida. The research was conducted with a cross-sectional design using questionnaires and Hamilton Rating Scale Anxiety (HRS-A). Interviews were conducted on 43 primigravida and multigravidae pregnant women on 3rd trimester who checkup at Public Health Center (PHC) of Talango, Sumenep. The sample was taken by simple random sampling. Independent variables in this study were maternal characteristics, internal and external factors which cause anxiety. The dependent variable was the level of anxiety in facing labor. The testing difference in the level anxiety in the face of labor between primigravida and multigravida with Wilcoxon Mann-Whitney U test, where statistic values sig. (2-tailed) is 0,006 or p<0,05 indicating that there were differences in anxiety levels between primigravida and multigravida. The conclusion that can be drawn is that there are differences in the level of anxiety in facing childbirth between primigravida and multigravida. It is recommended for health workers to concern not only on the pregnancy but also on the mother’s psychology condition. Health workers should inform husbands to accompany their wives from pregnancy to childbirth.